A flexible and stretchable photonic crystal sensor for biosensing and tactile sensing. Issue 11 (November 2022) - Peng, Wang; Huang, Bing; Huang, Xuanxuan; Song, Han; Liao, Qingxi
Abstract: Biosensing and tactile sensing are considered to be essential functions for intelligent diagnostic medical robot. In this paper, biosensing and tactile sensing had been demonstrated with a single photonic crystal structure. The flexible and stretchable photonic crystal structure consists of PDMS as the flexible substrate and TiO2 as the guided layer, and the nanograting structure was realized by nanoreplica molding. For biosensing experiment, a sensitivity of 93 nm/RIU is verified with ambient environment RI variance simulation results. For tactile sensing experiment, the highest resolution for strain sensing is 0.1%, and the minimum detected scale of the grating period variation is 0.1 nm. The TiO2/PDMS structure based flexible and stretchable photonic crystal sensor demonstrates highly sensitivity and potentially cost effective for biosensing and tactile sensing, and it is promising in the area of intelligent diagnostic medical robot. Abstract : Flexible and stretchable photonic crystal; Tactile sensing; Biosensing; Nanoreplica molding